PEDAGOGICAL CONDITIONS FOR THE FORMATION OF LANGUAGE CULTURE IN 4TH GRADE STUDENTS IN LANGUAGE LESSONS BY ORAL FOLK ART (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the problem of speech culture organization for the 4-th form pupils at the native language lessons by means of folklore (spoken people’s creative work).The folklore promotes organization of the following positive qualities of the rising generation such as: audacity, honesty, adherence to principles, kindness and truthfulness, while using saying and proverbs in their speech pupils learn how to expound their thoughts and feelings clearly and laconicly, to put an intonation complexion on their speech and develop their ability to use a word creatively.